Analysis of 11 Trials Comparing Muscle-Sparing with Posterolateral Thoracotomy - Li, Shikang; Feng, Zhiqiang; Wu, Lishuo; Huang, Qiangxin; Pan, Shangling; Tang, Xianyan; Ma, Buguo (The Thoracic and Cardiovascular Surgeon, 2014)
Background Muscle-sparing thoracotomy (MST) has recently been developed in an attempt to minimize tissue injuries during thoracic operation and postoperative sequelae. However, its potential advantages over traditional posterolateral thoracotomy (PLT) remain to be determined. Here, we performed a meta-analysis on all available studies that compare the pros and cons between the two approaches.Methods A total of 11 relevant studies were found to satisfy our inclusive criteria from three electronic databases. End points included postoperative pain, pulmonary function, postoperative mortality, and perioperative complications.Results Data from seven randomized controlled trials and four observational studies were included (n = 408 and 564, respectively). Compared with PLT group, MST group had a significantly reduced postoperative visual analog scale score on day 1 (weighted mean difference [WMD], −0.79; 95% confidence interval [CI], −1.10 to −0.48), week 1 (WMD, −0.60; 95% CI, −0.98 to −0.22), and month 1 (WMD, −0.73; 95% CI, −1.30 to −0.16). However, no difference between the two approaches was found on postoperative forced vital capacity and forced expiratory volume in 1 second (week 1: standardized mean difference [SMD], 0.44; 95% CI, −0.18 to 1.07 versus SMD, 0.53; 95% CI, −0.13 to 1.18; month 1: SMD 0.26; 95% CI, −0.26 to 0.78 versus SMD, 0.38; 95% CI, −0.25 to 1.00), mortality (odds ratio [OR], 1.23; 95% CI, 0.49 to 3.09), and complications (OR, 0.86; 95% CI, 0.60 to 1.23).Conclusions MST may improve postoperative pain, but shows less effect on other perioperative parameters.
Keywords: surgery/incisions; chest wall; pulmonary function; surgery; complications; outcomes (includes mortality and morbidity)